(untitled) (Journal of Hama University, 2025)
Abstract: The aim of the research is to determine the degree of use of voice awareness skills in the introductory book of the Arabic Language Learner Series for non-Arabic speakers and to envisage a proposal to enrich it. The analytical descriptive methodology was used. The sample consisted of research from the training and activities contained in the preliminary book. The researcher used the content analysis form. The total number of analytical units in the content of the preliminary book of the Lyssan series (154) has reached an analytical unit. It was ranked first in favour of the skills of voice awareness repeated (144) and the ratio (93.50%), followed by the second by the skill of word awareness repeated (10) and the percentage (6.49%), while the presence of the skill of the awareness of the passage was no (0%). Focus its attention on acquiring learners some skills that relate to distinguishing between short and long movements, and neglect many skills that have an important role to play in mastering learners’ voice system. Differences in relative weights of skills, indicating random distribution of content. Keywords: Skill _ Voice Awareness _ Preliminary Book _ Tongue Series_ A proposal.